Enhancing spectral efficiency with low complexity filtered-orthogonal frequency division multiplexing in visible light communication system - Hayder S. R. Hujijo; Muhammad Ilyas (ETRI Journal)
The filtered-orthogonal frequency division multiplexing (F-OFDM) scheme has gained attention as a promising solution in the field of visible light com-munication (VLC) systems. One crucial aspect in VLC is the conversion of the complex F-OFDM signal into a real signal that corresponds with direct detec-tion and intensity modulation. Traditionally, achieving a real F-OFDM signal has involved imposing Hermitian symmetry (HS) on the samples of the Inverse Fast Fourier transform (IFFT), which requires 2N-point IFFT and obtains an N-point FFT, thus adding complexity. In this study, a novel approach is presented and implemented, aiming to enhance spectral efficiency and reduce system complexity by generating a real F-OFDM signal without relying on HS. This approach is then compared with HS-free (HSF)-OFDM, direct current biased optical OFDM, and asymmetrically clipped optical OFDM. The suggested method offers a remarkable improvement of ?50% in the required IFFT/FFT volume. Consequently, this method reduces hardware complexity and power usage compared with the traditional F-OFDM method. Moreover, regarding error rates, the proposed method demonstrates better spectral efficiency than HSF-OFDM.